2016
DOI: 10.1111/ijal.12151
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of SA and intensive AH courses on teenagers' L2 pronunciation

Abstract: The present study compares the differential effects of two learning contexts on the L2 pronunciation accuracy of L1‐Spanish/Catalan teenage learners of English. The learners engaged in either a study abroad (SA) course in the UK (n = 14) or in an intensive course at home (AH) in Spain (n = 22) for 3 weeks. Sentence‐sized production samples were elicited before and after the SA and AH courses through a delayed imitation task targeting difficult L2 phonetic and phonological features. L2 pronunciation accuracy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Over nearly three decades, there has been an increase in research investigating the effectiveness of study abroad programs on varied facets of language development. The foci of the prior empirical studies include the development of speaking (Freed, 1995; Llanes, 2012; Llanes et al, 2017; Solon & Long, 2018), reading (Dewey, 2004; Li, 2014), writing (Llanes, 2012; Sasaki, 2007; Serrano at al., 2016) and listening (Cubillos, Chieffo, & Fan, 2008; Taguchi, 2011) proficiency. Additional research investigated the acquisition of vocabulary knowledge (Zaytseva, Pérez-Vidal, & Miralpeix, 2018), utilizing new and different communication strategies (Lafford, 2004; Yashima & Zenuk-Nishide, 2008), and how L2 learners can gain proficiency in terms of grammatical (Isabelli-García, 2010; Marqués-Pascual, 2011; Sagarra & LaBrozzi, 2018;), pragmatic (Ren, 2015; Taguchi, 2011), and sociolinguistic abilities (Barron, 2006; Regan, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Over nearly three decades, there has been an increase in research investigating the effectiveness of study abroad programs on varied facets of language development. The foci of the prior empirical studies include the development of speaking (Freed, 1995; Llanes, 2012; Llanes et al, 2017; Solon & Long, 2018), reading (Dewey, 2004; Li, 2014), writing (Llanes, 2012; Sasaki, 2007; Serrano at al., 2016) and listening (Cubillos, Chieffo, & Fan, 2008; Taguchi, 2011) proficiency. Additional research investigated the acquisition of vocabulary knowledge (Zaytseva, Pérez-Vidal, & Miralpeix, 2018), utilizing new and different communication strategies (Lafford, 2004; Yashima & Zenuk-Nishide, 2008), and how L2 learners can gain proficiency in terms of grammatical (Isabelli-García, 2010; Marqués-Pascual, 2011; Sagarra & LaBrozzi, 2018;), pragmatic (Ren, 2015; Taguchi, 2011), and sociolinguistic abilities (Barron, 2006; Regan, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Learning context has been recognized as a key factor influencing second language acquisition (SLA) since the 1970s (Hymes, 1974). In particular, the last few decades have seen a sharp rise in empirical research investigating the effects of study abroad language programs on L2 acquisition (Dekeyser, 1991;Freed, 1995;Freed, Segalowitz & Dewey, 2004;Hirakawa, Shibuya, & Endo, 2019;Llanes, Mora & Serrano, 2017;Schenker, 2018). It is generally believed that studying a language abroad provides L2 learners with opportunities to employ the target language in real-life situations including through local media and cultural events than studying the L2 domestically.…”
Section: Introductionmentioning
confidence: 99%
“…However, SA research has revealed that not all L2 areas are positively affected after an overseas experience. Although many studies conclude that SA is a good weapon towards language improvement (Juan-Garau, 2014; Michell, Tracy-Ventura, & VIAL n_17 -2020 McManus, 2017), the same attention has not been given to all the L2 areas: There are many studies on oral skills (George, 2014;Llanes, Mora, & Serrano, 2016), but other areas such as reading require further investigation. As Kinginger (2009:61) stated "competence in reading is remarkably under-represented in the applied linguistics literature related to study abroad".…”
Section: Sa and L2 Reading Developmentmentioning
confidence: 99%
“…There is evidence that short (≤ 5 weeks) SA experiences have a positive impact on several L2 areas, such as oral skills (Llanes & Muñoz, 2009), pragmatic development (Reynolds-Case, 2013), listening comprehension (Cubillos, Chieffo, & Fan, 2008;Rodrigo, 2011), pronunciation (Llanes, Mora, & Serrano, 2016), and writing skills (Evans & Fisher, 2005). However, there is no single study, to the authors' knowledge, that looks at the impact that such a short SA experience has on L2 vocabulary, and there is only one that includes reading development (Evans & Fisher, 2005), although learning vocabulary is usually among the short-SA participants' goals (Allen, 2010) and reading is one of the most important skills (Rasinski, 2003).…”
Section: Sa and L2 Vocabulary Developmentmentioning
confidence: 99%
“…Neither study found significant differences between the SA and AH groups. However, Llanes et al (2017) found that L2 English (L1 Spanish-Catalan) speakers in the SA context increased their VOT (more English-like [p h , t h , k h ]) than AH speakers. Contrasting findings may be due to methodological differences between studies (i.e., number of participants, tasks, number of tokens, acoustic vs. auditory analysis).…”
Section: Introductionmentioning
confidence: 99%